THE RELATIONSHIP AMONG LEARNERS’ SELF-EFFICACY, THEIR ENGLISH PROFICIENCY AND THEIR CONTENT AREA SUBJECT ACHIEVEMENT - Ida Isnawati (Jurnal Bahasa Lingua Scientia, 2013)
This study investigated the relationships among the learners’ self-efficacy, their English proficiency and their content area subject achievement. The researcher took the data of those variables and tested the hypothesis using 32 samples of English Study Program students at STAIN Tulungagung. The results obtained revealed that there was a significant positive relationship between the learners’ self-efficacy and their achievement in content area subject, but no significant relationship between their self-efficacy and their English proficiency. The learners’ English proficiency was also correlated with their content area subject achievement. Thus, in general, it can be concluded that the three variables have relationships although they have different degree of relationships.